S7 Mortality following assessment for pulmonary rehabilitation (PR) in patients with COPD: a preliminary analysis from the 2015 national COPD: PR audit. (December 2018) - Evans, RA; Lowe, D; McMillan, V; Blakey, J; Beckford, K; Bolton, CE; Elkin, S; Greening, NJ; Man, WDC; Sewell, L; Singh, SJ; Walker, P; et al.
Abstract : Background: The recent National COPD Audit: Pulmonary Rehabilitation (PR) report 1 indicated completion of PR was associated with a survival advantage at 180 days. We investigated whether this was related to the effects of PR or to confounding due to differences in case-mix severity. Methods: PR services across England and Wales provided data for all consenting patients assessed for PR between Jan and April 2015. Mortality data were extracted from the Office for National Statistics (ONS) from Jan 2015 – Jan 2017. Time to event analysis was performed until Jan 2017 using Cox proportional hazards model adjusted for baseline gender, age [yr], FEV1 [L], Body Mass Index (BMI) category, MRC dyspnoea grade, smoking status, presence of co-morbidities and Incremental Shuttle Walk distance (ISWT) [m]. Results: 1755 patients had complete datasets for all components of the model: 53% male, mean [SD] age 69 [9] yrs, FEV1 1.38 [0.59] L, median BMI category 'overweight', MRC 1: 2%, 2: 21%, 3: 38%, 4: 32%, 5: 7%, 7% never smokers, 71% ex-smokers, 22% current smokers, 92% other co-morbidity, ISWT 212 (135) m. n=67 patients who likely died before completion of PR were removed (date of death Jan – May 2015). The unadjusted mortality rate was 7.2% for those who completed PR vs 7.8% for those who did not, p=0.74 [figure 1]. Completion of PR was not significantly associated with mortality after adjustment, HR (95% CI) 1.03 (0.69 to 1.05, p=0.88) whereas older age 1.03 (1.01 to 1.05, p=0.008), male gender 1.87 (1.30 to 2.70, p=0.001), higher FEV1 0.69 (0.48 to 0.98, p=0.04), higher BMI category 0.72 (0.62 to 0.92, p<0.001), higher ISWT distance 0.99 (0.995 to 0.997, p<0.001) were all prognostic indicators in the final model. Conclusion: Cumulative mortality following PR is not significantly different between completers and non-completers after adjustment for baseline case-mix severity. However, exercise performance remains a modifiable prognostic indicator. Reference: https://www.rcplondon.ac.uk/projects/outputs/pulmonary-rehabilitation-beyond-breathing-better